2019
DOI: 10.1002/tox.22839
|View full text |Cite
|
Sign up to set email alerts
|

Inhaled Kathon may induce eosinophilia‐mediated disease in the lung

Abstract: In 2011, a link between humidifier disinfectants and patients with idiopathic pulmonary fibrosis was identified in Korea, and Kathon was suggested as one of the causative agents. In this study, Kathon induced apoptotic cell death along with membrane damage at 24 h post-exposure. Additionally, on day 14 after a single instillation with Kathon, the total number of pulmonary cells and the levels of TNF-α, IL-5, IL-13, MIP-1α, and MCP-1α clearly increased in the lung of mice. The proportion of natural killer cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…Forty-eight published studies using non-human animal subjects or in vitro toxicology studies were included in the review ( Table 3 ). 16 39 40 41 42 43 44 60 61 62 63 64 65 66 67 68 69 70 71 72 73 74 75 76 77 78 79 80 81 82 83 84 85 86 87 88 89 90 91 92 93 94 95 96 97 98 99 100 To investigate the hazardous effects of humidifier disinfectants, in vitro studies were performed using various cell lines, and toxicity tests were performed using several animal models. Cytotoxicity, lung fibrosis, and pulmonary genotoxicity due to PHMG exposure were described as a consequence of toxicity testing undertaken shortly after HDLI was reported.…”
Section: Resultsmentioning
confidence: 99%
“…Forty-eight published studies using non-human animal subjects or in vitro toxicology studies were included in the review ( Table 3 ). 16 39 40 41 42 43 44 60 61 62 63 64 65 66 67 68 69 70 71 72 73 74 75 76 77 78 79 80 81 82 83 84 85 86 87 88 89 90 91 92 93 94 95 96 97 98 99 100 To investigate the hazardous effects of humidifier disinfectants, in vitro studies were performed using various cell lines, and toxicity tests were performed using several animal models. Cytotoxicity, lung fibrosis, and pulmonary genotoxicity due to PHMG exposure were described as a consequence of toxicity testing undertaken shortly after HDLI was reported.…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, direct or indirect exposure to disinfectants through the respiratory system can cause adverse health effects as evidenced by the humidifier disinfectant incident in Korea, and interstitial fibrosis known as idiopathic pulmonary fibrosis is a representative disease. In previous studies, we demonstrated the main causative substances of the humidifier disinfectant event that occurred in Korea induced apoptotic cell death by impairing the cell membrane and mitochondria in BEAS-2B cells, a human bronchial epithelial cell line ( Park et al, 2020a ; Park and Seong, 2020 ; Park et al, 2020b ; Park et al, 2018 ). We also emphasized the possible application of the critical micelle concentration of the corresponding disinfectant as a method to predict the concentration at which toxicity may be induced.…”
Section: Discussionmentioning
confidence: 98%
“…A recent study performed by our research group showed that Kathon induces apoptotic cell death along with membrane damage in human bronchial epithelial (BEAS-2B) cells [ 10 ], while, several inflammatory responses, including total number of BALF cells and the levels of TNF-α, IL-5, IL-13, MIP-1α, and MCP-1α, were markedly increased in the lung of Institute of Cancer Research (ICR) mice after single instillation with Kathon. The proportion of natural killer cells and eosinophils were also significantly elevated in the spleen and blood, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…This effect has been clinically confirmed in several human cases in which HD products containing a mixture of CMIT/MIT have been used in the home [ 9 ]. Further, a recent study demonstrated that Kathon may induce eosinophilia-mediated lung disease [ 10 ] and cause atopic dermatitis symptoms via dysregulation of Th2/Th17-related immune responses [ 11 ].…”
Section: Introductionmentioning
confidence: 99%